Anticorpos monoclonais contra as proteínas LigA e LigB de leptospiras patogênicas:produção e caracterização - Seyffert, Núbia (2007)
Leptospiral immunoglobulin-like (Lig)proteins are exposed on membrane surface of pathogenic Leptospira and may play a role in host cell attachment and invasion during infection.A pair of Ligs,named LigA and LigB,with identical and non-identical polypeptide regions has recently been identified.The two proteins elicit a strong humoral immune response during acute host infection and have been suggested as targets for development of vaccines and diagnostic tests for leptospirosis.This study reports the production and characterization of monoclonal antibodies (Mabs)against recombinant non-identical fragments of LigA (rLigANI)and LigB (rLigBNI).The recombinant fragments were used for mice immunization and screening hybridomas by indirect ELISA.Four Mabs obtained against rLigANI and six Mabs obtained against rLigBNI were isotyped and evaluated regarding their potential for use in studies of immunoprotection and diagnostic test development.The Mabs were of the IgM (1),Ig 2b (3)and Ig 1 (6)isotypes and reacted with the native proteins from a pathogenic strain of Leptospira i terroga s serovar Copenhageni L1 130 in an indirect ELISA and immunofluorescence.Mabs affinity constants felt between 4x10 7 M -1 and 2x10 8 M -1 ,and epitope mapping by additive ELISA has shown that each Mab either react with the same epitope in the recombinant molecule or cause steric hindrance. Tissue sections from kidneys of hamsters experimentally infected with leptospires and probed with the Mabs reacted positively by immunohistochemistry.These findings suggest that the Mabs obtained can be useful for the studies of immunoprotection and development of diagnostic tests.